An Obstacle for Higher Regularity of Geodesics in the Space of Kähler Potentials. (1st August 2019) - Hu, Jingchen
Abstract: In this paper we address the following question regarding the regularity of geodesics in the space of Kähler potentials. Given a geodesic that is highly regular, and has smooth boundary value, can we expect that it is actually smooth? We construct an example to show that the answer to the question is "no".